Co‐designing a theory‐informed, multicomponent intervention to increase vaccine uptake with Congolese migrants: A qualitative, community‐based participatory research study (LISOLO MALAMU) - Alison F. Crawshaw; Lusau M. Kitoko; Sarah L. Nkembi; Laura M. Lutumba; Caroline Hickey; Anna Deal; Jessica Carter; Felicity Knights; Tushna Vandrevala; Alice S. Forster; Sally Hargreaves (Wiley, 2024)
Abstract Introduction Disparities in the uptake of routine and COVID‐19 vaccinations have been observed in migrant populations, and attributed to issues of mistrust, access and low vaccine confidence. Participatory research approaches and behaviour change theory hold the potential for developing tailored vaccination interventions that address these complex barriers in partnership with communities and should be explored further. Methods This study used a theory‐informed, community‐based participatory research approach to co‐design a culturally tailored behaviour change intervention aimed at increasing COVID‐19 vaccine uptake among Congolese migrants in London, United Kingdom (2021-2022). It was designed and led by a community‐academic partnership in response to unmet needs in the Congolese community as the COVID‐19 pandemic started. Barriers and facilitators to COVID‐19 vaccination, information and communication preferences, and intervention suggestions were explored through qualitative in‐depth interviews with Congolese migrants, thematically analysed, and mapped to the theoretical domains framework (TDF) and the capability, opportunity, motivation, behaviour model to identify target behaviours and strategies to include in interventions. Interventions were co‐designed and tailored in workshops involving Congolese migrants. Results Thirty‐two Congolese adult migrants (24 (75%) women, mean 14.3 (SD: 7.5) years in the United Kingdom, mean age 52.6 (SD: 11.0) years) took part in in‐depth interviews and 16 (same sample) took part in co‐design workshops. Fourteen barriers and 10 facilitators to COVID‐19 vaccination were identified; most barrier data related to four TDF domains (beliefs about consequences; emotion; social influences and environmental context and resources), and the behavioural diagnosis concluded interventions should target improving psychological capability, reflective and automatic motivations and social opportunities. Strategies included culturally tailored behaviour change techniques based on education, persuasion, modelling, enablement and environmental restructuring, which resulted in a co‐designed intervention comprising community‐led workshops, plays and posters. Findings and interventions were disseminated through a community celebration event. Conclusions Our study demonstrates how behavioural theory can be applied to co‐designing tailored interventions with underserved migrant communities through a participatory research paradigm to address a range of health issues and inequalities. Future research should build on this empowering approach, with the goal of developing more sensitive vaccination services and interventions which respond to migrant communities' unique cultural needs and realities. Patient or Public Contribution Patient and public involvement (PPI) were embedded in the participatory study design and approach, with community members co‐producing all stages of the study and co‐authoring this paper. An independent PPI board (St George's Migrant Health Research Group Patient and Public Involvement Advisory Board) comprising five adult migrants with lived experience of accessing healthcare in the United Kingdom were also consulted at significant points over the course of the study.